Structural Properties of the Quaternary Alloy CuIn(SxSe1-x)2 - Awitdrus Awitdrus; Yanuar Yanuar (Institut Teknologi Bandung, 2002)
In this paper we report the structural characterization of the quaternary alloy CuIn(SxSe1-x)2 grown by the horizontal Bridgman method. It is found that the CuIn(SxSe1-x)2 crystals have a chalcopyrite structure. With increasing x, lattice constants decrease following Vegard’s law.